PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI DENGAN MODEL PEMBELAJARAN BERDIFERENSIASI SISWA KELAS V SD NEGERI TLOGO - Findy Yonanta, Apriliya; Rigianti, Henry Aditia; Purnomo, Heru (Jurnal Dikdas Bantara, 2024)
This research is classroom action research which aims to improve literacy and numeracy skills through a differentiated learning model in mathematics learning. This research was conducted at Tlogo State Elementary School with respondents from class V students, numeracy literacy in class 5 was still low between literacy and numeracy which decreased further, namely in numeracy because class 5 students were lazy in calculating porogapit mathematics questions. This type of research is classroom action research, using the Kemmis and Mc Taggart model, in the order of planning, acting, observing, reflecting. The data collection technique uses tests by giving porogapit questions to students. The data analysis technique used in this research is a correlational analysis technique using the normality test with the Kolmogrov-Smirnow test. The success indicator for this research is said to be successful if the average percentage of each indicator of student activity reaches 75%. The research results show that the differentiated learning model can improve literacy and numeracy. The percentage result in cycle I was 42% and then in cycle 72%, so it was said to be successful because it met the success criteria